2015
DOI: 10.1073/pnas.1422872112
|View full text |Cite
|
Sign up to set email alerts
|

MOZ and BMI1 play opposing roles during Hox gene activation in ES cells and in body segment identity specification in vivo

Abstract: Hox genes underlie the specification of body segment identity in the anterior-posterior axis. They are activated during gastrulation and undergo a dynamic shift from a transcriptionally repressed to an active chromatin state in a sequence that reflects their chromosomal location. Nevertheless, the precise role of chromatin modifying complexes during the initial activation phase remains unclear. In the current study, we examined the role of chromatin regulators during Hox gene activation. Using embryonic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Moz mRNA is expressed widely in most or all cells at all stages of mouse embryonic development examined (E7.5, E8.5, E9.5, E10.5 and E13.5), including in the maxillary component of the first pharyngeal arch, which gives rise to the secondary palate (Sheikh et al, 2015a;Thomas et al, 2006;Voss et al, 2009). We have previously reported craniofacial defects in MOZ-deficient mouse foetuses, including micrognathia and a complete cleft of the secondary palate (Voss et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Moz mRNA is expressed widely in most or all cells at all stages of mouse embryonic development examined (E7.5, E8.5, E9.5, E10.5 and E13.5), including in the maxillary component of the first pharyngeal arch, which gives rise to the secondary palate (Sheikh et al, 2015a;Thomas et al, 2006;Voss et al, 2009). We have previously reported craniofacial defects in MOZ-deficient mouse foetuses, including micrognathia and a complete cleft of the secondary palate (Voss et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Sas3-Rfc1 and Enok-Elg1 interactions suggest an evolutionarily conserved link between the KAT6 complexes and the RFClike complexes. Second, MOZ has been shown to genetically interact with the polycomb protein BMI1 in regulating HOX gene activation (60). Together with the finding that Enok copurified with the repressive PRC1 complex (49), these observations suggest that the activator KAT6 complex may associate with PRC1 at specific gene loci to dynamically regulate gene expression during development.…”
Section: Roles Of Kat6 Hats In Cell Cycle Regulation and Stem Cell Mamentioning
confidence: 90%
“…MOZ can interact with AML1 and PU.1, two essential transcriptional factors for hematopoiesis, and enhance AML1-and PU.1-dependent transcription (57,58). Furthermore, several studies have shown that MOZ activates the expression of HOX genes in embryos and blood cells by acetylating H3K9 (30,42,59,60), suggesting another mechanism underlying the roles of MOZ in hematopoiesis, since HOX genes are critical for the development of the hematopoietic system (reviewed in reference 61). Similar to the importance of MOZ in hematopoietic stem cell renewal, both MOZ and BRPF1 are involved in the maintenance of neural stem cells (55,62), raising the possibility that the MOZ complex has a general role in maintaining stem cells.…”
Section: Roles Of Kat6 Hats In Cell Cycle Regulation and Stem Cell Mamentioning
confidence: 99%
“…Our results are consistent with recent studies in which PRC1 is found on active genes in many systems (Schaaf et al 2013;Pemberton et al 2014;van den Boom et al 2016), and PRC1 targeting is largely independent of PRC2 (Kahn et al 2016). Most exciting is the likely conservation in zebrafish (Laue et al 2008) and mice (Sheikh et al 2015), based on the opposing genetic activities of PRC1 and MOZ/MORF complexes in regulation of the Hox genes. The reliance on a universal transducer of transcription factor activity in developmental decisions would be an elegant solution to the problem of widespread binding of sequence-specific regulators, as, in our model, only local interactions with preset bivalency will result in functional consequences.…”
Section: Discussionmentioning
confidence: 99%